The esthetic features of the mysterious and playful in the art world Leskov’s works (“Negleted People”, “Christmas Stories”, “The Devil Dolls”) - Скубачевська, Любов Олександрівна; Титова, Олександра Сергіївна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2019)
The relevance of the subject is determined by the growing interest of contemporary literary criticism to the problem of the spiritually mysterious aspects of human nature and behavior described in the Leskov’s art. The author brings it closer to the New Literature of the turn of the 19–20 centuries.The purpose of the article is the characterization of esthetic mysterious and playful features the Leskov’s art. The object of the work is study the novel “The ghost in the Engineering Castle” belonging to the “Christmas Stories” (1889) and “Neglected People” (1865) and “The Devil Dolls” (1891). These works are distinguished by genres and time of writing. On the other hand, the existence of mysterious, deception, switch, masquerade, dream motives unites these novels. This fact defines the study matter.As it turned out, Leskov uses literary devices such as parody, caricature, black humor, poetics of masquerade, dreams and fantasy, complicated storylines, etc. All of them relate to the poetics of game. The most important among them are changing the points of view, the game with the reading expectations and the author’s irony.As a whole, researched motives, methods, the poetics of game and the experiments with the genre show us Leskov’s artistic innovation, “transitional” phenomenon in the literature of the end of 19 century. Either it shows us certain convergences with New Prose of the turn of 19 and 20 centuries. Furthermore, the research has shown that Leskov uses the game to find out the signs of human being mystery in everyday life. His fact transfers the prose perception from the moral and psychological field to ontology.